Implementation of Content Based Filtering Algorithm in Comic Recommendation System - Alana, Reyhan; Hartanto, Adi (Sistemasi: Jurnal Sistem Informasi, 2024)
Currently, the interest of comic readers in Indonesia is increasing and has become a popular culture. With so many comics released each year, it makes it difficult for the readers to find comics that fulfill their criteria, therefore the recommendation system becomes a feature that is quite important and has a role in helping the readers. The data used is comic data totaling 1219 comics, with details of 471 physical comics published by Elex Media Komputindo publishers and 748 digital comics released on the Line Webtoon Indonesia platform. This research uses the Content Based Filtering algorithm because it only utilizes title and synopsis data from the comic. The Cosine Similarity method is used to calculate the similarity value of a comic data with the criteria that has been entered and can test the data 10 times until the system successfully gives suitable comic recommendations with an average precision score of 94.86%.